Rancang Bangun Sistem Pultrusi Arduino Berbiaya Rendah dengan Kontrol Pemanas dan Pemotong Terintegrasi untuk Mengolah Limbah Botol PET menjadi Filamen 3D Printing - Aristo Bima; Nur Abdillah Siddiq; Panji Dewandaru; Thomas Oka (Jurnal Otomasi Kontrol dan Instrumentasi, 2025)
Plastic waste, particularly polyethylene terephthalate (PET) bottles, has emerged as a critical global challenge. Single-use plastic production has continued to increase, while Indonesia generates millions of tons of waste annually, with a significant portion being plastic. To address this issue, this study presents the design of a low-cost Arduino-based pultrusion system for recycling PET bottles into 3D printing filament. Unlike existing open-source solutions that rely on manual or separate processing stages, the proposed system integrates heating, cutting, and cleaning modules into a single automated workflow with real-time control of motor speed and nozzle temperature. Experimental results show that filament tensile strength depends on pultrusion temperature, reaching 67.66 MPa at 195 °C, 62.08 MPa at 185 °C, and 58.64 MPa at 175 °C. Energy analysis indicates that the heater consumed of 0.203 kWh to reach the set-point and 0.509 kWh after one hour, while the pultrusion drive consumed 0.00233 kWh and 0.0257 kWh, respectively. Compared with values reported in prior studies, the tensile strength obtained is within or above typical PET filament ranges. These findings demonstrate that the developed system reduces manual handling, improves efficiency, and produces reliable, energy-efficient filament suitable for additive manufacturing.